2012
DOI: 10.5539/ibr.v5n9p120
|View full text |Cite
|
Sign up to set email alerts
|

Does Board of Director’s Characteristics Affect Firm Performance? Evidence from Malaysian Public Listed Companies

Abstract: The aim of this study is to answer the question: "do board characteristics affect firm performance?" There are six board of directors' characteristics being studied, including managerial ownership, board size, board independence, CEO duality, gender diversity and ethnic diversity. Return on Equity (ROE) is used as a measurement for firm financial performance. There are 300 Malaysian public listed companies being randomly selected from each sector. The results show that board size and ethnic diversity have posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
120
4
14

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(162 citation statements)
references
References 13 publications
24
120
4
14
Order By: Relevance
“…[20] found insignificant association between a CEO holding dual roles as chairman and income-increasing and income-decreasing earnings management among Malaysian firms, supporting the findings of [21]. [22] too yielded insignificant correlation between the CEO-duality role and return on equity. In an earlier study, [23] revealed significant evidence of the relationship between role duality and performance measure in return on assets and return on equity.…”
Section: And) ) and ' "- "(") )! #And( +"#*( ) " And) !/ ' *(+ )And"-supporting
confidence: 71%
“…[20] found insignificant association between a CEO holding dual roles as chairman and income-increasing and income-decreasing earnings management among Malaysian firms, supporting the findings of [21]. [22] too yielded insignificant correlation between the CEO-duality role and return on equity. In an earlier study, [23] revealed significant evidence of the relationship between role duality and performance measure in return on assets and return on equity.…”
Section: And) ) and ' "- "(") )! #And( +"#*( ) " And) !/ ' *(+ )And"-supporting
confidence: 71%
“…The impact of corporate governance on firm performance has gained a considerable attention by researchers in recent years (Shukeri et al, 2012). The financial scandals in the US economy such as the collapse of Worldcom and Enron have increased the attention of a lot parties in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…However, mixed results exist in how board size affects firm profitability. Some studies showed a positive relationship between these two across a wide array of sample countries (Mak & Kusnadi, 2005;Shukeri, Shin, & Shaari, 2012;Zabri et al, 2016). However, contrasting findings were also found in some studies, as they demonstrated a negative association between firm size and profitability in both developed and emerging markets (Aldehayyat, Alsoboa, & Al-Kilani, 2016;Morekwa Nyamongo & Temesgen, 2013;Obradovich & Gill, 2012.…”
mentioning
confidence: 94%